Is the Imitative Competence an Asymmetrically Distributed Function? - Fabri, Mara; Pierpaoli, Chiara; Foschi, Nicoletta; Polonara, Gabriele (Frontiers in Systems Neuroscience, 2021)
This study reconsiders behavioral and functional data from studies investigating the anatomical imitation (AI) and the related mental rotation (MR) competence, carried out by our group in healthy subjects, with intact interhemispheric connections, and in split-brain patients, completely or partially lacking callosal connections. The results strongly point to the conclusion that AI and MR competence requires interhemispheric communication, mainly occurring through the corpus callosum, which is the largest white matter structure in the human brain. The results are discussed in light of previous studies and of future implications.